Effect of Shorter Cross Clamp Time vs. longer Cross Clamp time on cardiac enzyme levels in pts of CAD undergoing CABG - Syeda Rabia Mahmood, Ahsan Arif, Saima Jabeen, Hasan Hafeez, Ali Raza Ihsan, Aftab Yunus (Pakistan Journal of Medical & Health Sciences, 2023)
Aim: To compare mean cardiac enzyme levels in of shorter cross clamp time V/S longer cross Clamp time in patients undergoing CABG in local population. Study Design: Randomized Controlled Trial Place and duration: This study was performed from 2nd April 2020 to 2nd October 2020 in the Department of Cardiac Surgery Punjab Institute of Cardiology, Lahore. Methodology: After informed consent, all patients undergoing CABG were enrolled and divided into two groups. A predesigned performa was used to enter preop, intra op and post op variables and cardiac enzyme levels were compared between shorter (<60 minutes) and longer (>60 minutes) aortic cross clamp time groups. Results: Study had enrolled 300 patients and 150(50%) patients were designated group A (shorter cross clamp time and 150 (50%) patients were designated in group B (longer cross clamp time). Out of these 300, 246 patients (82%) were males and 54 (18%) were females. Extremes of age were 70 years and 37 years and mean age was 56.77±8.03 years. Group A (shorter cross clamp time) patients had mean age of 56.64 ±7.53 and group B (longer cross clamp time) patients had 56.89±8.52 .Mean EF (%) was 52.17±8.98 with 23% being minimum and 70% being maximum. In group A patients, 93 patients (62%) were hypertensive , 82(55%) were smokers and 67 (45%) patients were diabetic, while group B had 110 (73%) hypertensive, 84(56%) smokers and 73(49%) diabetic patients. Mean CPB time in group A was recorded to be 93.72±29.97 and mean CPB time in group B was 121.04±31.83. The P-value was 0.001, significant enough to represent difference in CPG time in both groups Practical Implication: Additionally, no notable difference was found in need of inotropic supports between two groups. Longer cross clamp time is also associated with longer CPB time which in turn correlates with higher morbidity and mortality. Conclusion: It is concluded that prolonged cross clamp time is an independent predictor of morbidity despite cardio protection by modern strategies Keywords: CKMB, IABP, CABG, CPB time, aortic cross clamp time, Shorter Cross